Associated socioeconomic status with illness behavior in tuberculosis patients undergoing DOTS therapy - A, Munsab; S, Manju; Najmi, Abul Kalam; I, Faisal; M, Santanu; K M, Ravinder (Indian Journal of Pharmacy Practice)
The aim of the present study was to investigate whether socioeconomic status can influence the illness behaviour of tuberculosis patient. The present study was a prospective for which we compared tuberculosis patients (case, group-I) with other respiratory disease patients (control, group II) on the basis of illness behaviour questionnaire (IBQ) and observed for possible differences between the two patient subgroups. Number of patients enrolled for the study were 82 out of whom, 41 patients served as case (i.e. group-I) and 41 patients as control (i.e. group-II). Group-I received standard Directly Observed treatment Shortcourse (DOTS) therapy as per Revised National TB Control Program (RNTCP) guidelines and was categorized as illness behavior under DOTS therapy. The group-II diagnosed patients of chronic respiratory disease like Chronic Obstructive Pulmonary Disease (COPD), Asthma, Chronic bronchitis etc. by the respective physicians. The data were fed into the computer programme SPSS and odd Ratios (OR) along with Confidence intervals (CI) and p-value were calculated for all the items to find out difference between cases and controls, if any. The present study reveals that socioeconomic status in tuberculosis patients tends to develop more intense illness behaviour as compared to other respiratory disease patient. Tuberculosis not only affects the body but it also affects the behavior of the patients. Therefore, management of illness behaviour should also be included in management of tuberculous patients.
Keywords: Tuberculosis; DOTS; RNTCP; respiratory disorders